Nanotechnology-Based Drug Delivery Systems - Andrey N. Kuskov; Ekaterina V. Kukovyakina; Ekaterina N. Krasnoselskaya (Pharmaceutics)
Modern oncological and chronic inflammatory diseases require new approaches to drug therapy due to the limited effectiveness and several side effects of traditional drug preparations [...]